Effect of Olanzapine and Risperidone on prolactin level in schizophrenic patients (Tikrit Journal of Pharmaceutical Sciences, 2023)
Hyperprolactinemia is a well-established adverse effect associated with the use of typical and atypical antipsychotics. Hyperprolactinemia is associated with both acute and chronic clinical consequences in men and women. Increased prolactin levels received little attention and were rarely monitored. Therefore, the primary objective of this study is to investigate the effects of two atypical antipsychotics (olanzapine and risperidone) on prolactin level in schizophrenic patients. For this purpose, a therapeutic clinical trial was done. We prospectively recruited 28 schizophrenic patients attended to Social and Psychiatric Service Centre in Mosul city. All patients fulfilled the Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) criteria for schizophrenia. They were randomized to receive monotherapy with either olanzapine in a dose 5-20 mg or risperidone in a dose 4-12 mg for 8 weeks (two groups). Also 22 apparently healthy subjects with approximately age and sex matching to the patients groups without previous history of schizophrenia or any other psychiatric disorders were taken as a control group. This study shows that, at baseline, there were no significant differences between the three studied groups in term of prolactin level and, after treatment with these drugs for 8 weeks, both drugs caused a significant increase in the prolactin level compared to baseline levels and that risperidone causes significantly greater increase in the levels of prolactin than olanzapine